Exploiting chemically selective weakness in solids as a route to new porous materials - Morris, Russell E; Čejka, Jiří (Nature chemistry, 2015)
Weakness in a material, especially when challenged by chemical, mechanical or physical stimuli, is often viewed as something extremely negative. There are countless examples in which interesting-looking materials have been dismissed as being too unstable for an application. But instability with respect to a stimulus is not always a negative point. In this Perspective we highlight situations where weakness in a material can be used as a synthetic tool to prepare materials that, at present, are difficult or even impossible to prepare using traditional synthetic approaches. To emphasize the concept, we will draw upon examples in the field of nanoporous materials, concentrating on metal-organic frameworks and zeolites, but the general concepts are likely to be applicable across a wide range of materials chemistry. In zeolite chemistry, there is a particular problem with accessing hypothetical structures that this approach may solve.